A Dual Identity Approach for Conceptualizing and Measuring Children's Gender Identity. Issue 1 (1st June 2016) - Martin, Carol Lynn; Andrews, Naomi C. Z.; England, Dawn E.; Zosuls, Kristina; Ruble, Diane N.
Abstract : The goal was to test a new dual identity perspective on gender identity by asking children ( n =  467) in three grades ( M age  = 5.7, 7.6, 9.5) to consider the relation of the self to both boys and girls. This change shifted the conceptualization of gender identity from one to two dimensions, provided insights into the meaning and measurement of gender identity, and allowed for revisiting ideas about the roles of gender identity in adjustment. Using a graphical measure to allow assessment of identity in young children and cluster analyses to determine types of identity, it was found that individual and developmental differences in how similar children feel to both genders, and these variations matter for many important personal and social outcomes.